Pengaruh Sudut Chamfer Dan Gaya Tekan Akhir Terhadap Kekuatan Tarik Dan Porositas Sambungan Las Gesek Pada Paduan Al-Mg-Si. - Santoso, Eko Budi; Irawan, Yudy Surya; Sutikno, Endi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
to aluminum properties that make difficulty to produced good well joints.To overcome this problem,in this study,chamfer angles were used on both contact surfaces of friction welding specimens. Used chamfer angles were 15 0,30 0 45 0, 60 0 and 75 0, variation of upset load were 157 kgf, 185 kgf and 213 kgf. Specimen were friction welded with rotational speed of 1600 rpm, compressive force of 123 kgf for 120 seconds. Then porosity testing and tensile strength testing were performed. Result showed that tensile strength of friction welding joint becomes higher with decreasing of chamfer angel and increasing of upset load. Specimen with chamfer 15 0 and upset load of 213 kgf has maximum tensile strength of 140,45 MPa. Specimen with chamfer angel 75 0 and upset loading of 213 kgf has the smallest porosity of 0,21 %. Keywords: tensile strength, porosity, friction welding, chamfer angle, upset load and Al-Mg-Si